Endocytosis and intracellular traffic of cholesterol-PDMAEMA liposome complexes in human epithelial-like cells - Szymanowski, Felipe (2017)
Liposomes are generally used as delivery systems, as they are capable of encapsulating a wide variety of molecules (i.e. plasmids, recombinant proteins, therapeutic drugs). However, liposomal drug delivery have to fulfill different requirements, such as the effective internalization by the target cells and avoidance of the degradative activity of the intracellular compartments. The use of polymer lipid complexes (PLCs), by including different polymers in the liposome formulation, could improve internalization and intracellular release of drugs. The aim of the present work is to study the mechanisms of cellular uptaking and the intracellular trafficking of PLCs formed with cholesterol-poly(2-(dimethylamino)ethyl methacrylate) CHO-PDMAEMA and lecithin (LC CHO-PD). Calcein-loaded liposomes were used to determine cellular uptake and intracellular localization by flow cytometry and confocal microscopy. Incorporation of CHOPDMAEMA to lecithin liposomes enhanced the internalization capacity of PLCs. Internalization of PLCs by human epithelial-like cells (HEK-293) diminished at 4 ◦C, suggesting uptake by endocytosis. PLCs showed no co-localization with acidic compartments after internalization. Experiments with endocytosis inhibitors and co-localization of liposomes and albumin, suggested the caveolae endocytic pathway as the most probable route for intracellular trafficking of PLCs. In this work, we demonstrated an efficient uptake of LC CHO-PDs by human epithelial-like cells (HEK- 293) through the non-degradative caveolae endocytic pathway. The mode of internalization and the intracellular fate of liposomes under study, suggest a promising use of LC CHO-PDs as drug delivery systems.